(untitled) (Journal of Engineering, 2020)
The performance of photovoltaic (PV) panel having staggered metal foam fins was examined experimentally in Baghdad, Iraq. Three staggered metal foam fin configurations attached to the backside of the PV panel were studied. The measured parameters were front and back surfaces temperature, open voltage and current circuits, maximum power, and PV efficiency. It was noted that the maximum electrical efficiency enhancement was 4.7% for staggered metal foam fins (case III) than the reference PV panel. The operating temperature of the cell was increased when the value of solar intensity was high. Thereby, the electrical efficiency was decreased. It was found that the metal foam fins decreased the PV temperature by 2-3 oC.